Przegląd literatury koreańskiej ze względu na sposób tworzenia. Przekazy ustne i pisemne. Literatura pisana w języku koreańskim - Oleksiuk, Marlena (2024)
The Korean literature is closely related to the Chinese script. The Chinese script had a significant impact on the reception of literature because it was considered important and elegant, and in the days after the invention of Hangul, Koreans were divided on which script poetry should be written in. The Korean alphabet, Hangul, became popular only in the 20th century. Korean literature can be presented in two ways: by genre and chronologically. Historical events have a significant impact on works created at a given time. Just like in the Polish literature, in the Korean literature, historical periods, oppression from neighboring countries and political events are reflected in the works of writers of a given era. The subject matter of this article is a description of written and oral works on the Korean Penisula and the impact of language choice on literature. The research perspective focuses on literature written in the Korean language, and the research material is literature created after the invention of Hangul.
Keywords: pansori; hanja; gugyeol; idu; hyangchal; hangul